Decreased expression of vitamin D receptor may contribute to the hyperimmune status of patients with acquired aplastic anemia. (29th July 2015) - Yu, Wei; Ge, Meili; Lu, Shihong; Shi, Jun; Feng, Sizhou; Li, Xingxin; Zhang, Jizhou; Wang, Min; Huang, Jinbo; Shao, Yingqi; Huang, Zhendong; Zhang, Jing; et al.
Abstract: Acquired aplastic anemia (AA) is an immune‐mediated bone marrow failure syndrome. 1 α, 25‐Dihydroxyvitamin D3 [1, 25(OH)2 D3 ], the biologically active metabolite of vitamin D, is a critical modulator of immune response via binding with vitamin D receptor (VDR). Previous studies have established that 1, 25(OH)2 D3 and VDR were involved in the pathogenesis of some autoimmune diseases. In this study, we evaluated the involvement of 1, 25(OH)2 D3 and VDR on T‐cell responses in AA. Plasma 25(OH)D3 levels were comparable between patients with AA and healthy controls. Surprisingly, VDR mRNA was significantly lower in untreated patients with AA than in healthy controls. Subsequent in vitro experiments revealed that 1, 25(OH)2 D3 treatment suppressed the proliferation of lymphocytes and inhibited the secretion of interferon‐ γ, tumor necrosis factor‐ α, and interleukin‐17A, meanwhile promoting the production of transforming growth factor‐ β 1 in patients with AA. Moreover, 1, 25(OH)2 D3 inhibited the differentiation of type 1 and Th17 cells but induced the differentiation of type 2 and regulatory T cells. Interestingly, VDR mRNA was elevated in healthy controls after 1, 25(OH)2 D3 treatment, but not in patients with AA. In conclusion, decreased expression of VDR might contribute to the hyperimmune status of AA and appropriate vitamin D supplementation could partly correct the immune dysfunction by strengthening signal transduction through VDR in patients with AA.